THU0219 Retrospective evaluation of 180 patients who were diagnosed as undifferentiated connective tissue disease. (1st June 2001) - Doganavsargil, E; Oksel, F; Keser, G; Inal, V; Aksu, K
Abstract : Background: Objectives: To review the outcome and diagnosis of patients whose initial clinical and laboratory findings were suggestive of a well established and undifferentiated connective tissue disease (uCTD), without fulfilling the diagnostic criteria of any connective tissue disease. Methods: Medical records of patients being followed up by Ege University rheumatology department between 1990 and 1999 were retrospectively screened. The data of 478 patients, constituting 18% of the total, whose initial diagnosis was uCTD, were further investigated. Patients with missing data were omitted and only 180 patients having reliable and complete initial clinical and laboratory data with regular controls were included. Results: The mean ages of 180 patients (F/M:173/7) at the time of initial clinical symptoms and at the time of diagnosis of uCTD were 35 ± 12 years and 38 ± 12 years, respectively. The distribution of initial symptoms and clinical findings were as follows: arthralgia/arthritis 97.2%, Raynaud phenomenon (RP) 30.5%, mucocutaneous findings 68.2%, symptoms of keratoconjunktivitis sicca 14.4%. It was notable that none of the patients had presented with initial symptoms or clinical finding reflecting direct involvement of a specific organ. In the final evaluation, 46 out of 180 patients (25.5%) were found to evolve into a definite clinical diagnosis: Sjögren's syndrome 21 (11.6%), systemic lupus erythematosus 8 (4.4%), rheumatoid arthritis 8 (4.4%), CREST syndrome 7 (3.8%), diffuse systemic sclerosis 1 and seronagative polyarthritis 1. In 5 patients a nonrheumatologic diagnosis was made, while in 11 patients fibromyalgia was diagnosed. The diagnosis of 118 (65%) patients (F/M:115/3) remained unchanged. The evaluation of initial clinical and laboratory parameters with respect to their contribution to final diagnosis revealed that, presence of Raynaud phenomenon and anti-centromeric antibodies were highly suggestive of later diagnosis of limited ScS. On the other hand, anti-dsDNA antibodies, leucopenia and thrombocytopenia, which are important parameters in well established SLE, were initially unpredictive of later SLE development in patients whose initial diagnosis was uCTD. Conclusion: In most of the patients whose initial diagnosis was uCTD, the disease tends to remain undifferentiated.